2020
DOI: 10.3390/w12102757
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Extreme Weather Events on Bacterial Community Composition of a Temperate Humic Lake

Abstract: Extreme weather events are projected to increase in frequency and intensity as climate change continues. Heterotrophic bacteria play a critical role in lake ecosystems, yet little research has been done to determine how they are affected by such extremes. The purpose of this study was to use high-throughput sequencing to explore the bacterial community composition of a humic oligotrophic lake on the North Atlantic Irish coast and to assess the impacts on composition dynamics related to extreme weather events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Hoke et al . (2020) studied the impact of seasonal storms on FL and PA bacterial communities and found that parts of the BC in the water column are more responsive to physical changes than others. Based on our results, it can be assumed that a part of the PA community (the LPA) experiences more significant structural changes due to particles of different sizes that enter the lake during rainfall and the sediment re‐suspension that can occur during storms (Hawley, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoke et al . (2020) studied the impact of seasonal storms on FL and PA bacterial communities and found that parts of the BC in the water column are more responsive to physical changes than others. Based on our results, it can be assumed that a part of the PA community (the LPA) experiences more significant structural changes due to particles of different sizes that enter the lake during rainfall and the sediment re‐suspension that can occur during storms (Hawley, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This spatio-temporal change in the bacterial structure in September especially the Verrucomicrobial increase occurred as a response to the sudden precipitation event and was only reflected in the LPA, not in the FL nor SPA communities (Figs S4, S7). Hoke et al (2020) studied the impact of seasonal storms on FL and PA bacterial communities and found that parts of the BC in the water column are more responsive to physical changes than others. Based on our results, it can be assumed that a part of the PA community (the LPA) experiences more significant structural changes due to particles of different sizes that enter the lake during rainfall and the sediment re-suspension that can occur during storms (Hawley, 2000).…”
Section: Increase Of Rainfalls and Temperature Drop At The End Of The...mentioning
confidence: 99%
“…The average path distance was longer and the positive edge proportion was smaller in the HL, which indicated that the interactions between functional genes in the HL might be less efficient and respond less quickly to the changes in the environment than those in the RAL. Some studies have shown that the bacterial communities in a humic lake were relatively resilient to extreme weather events [ 53 ]. In addition, there was higher resource availability in the HL water (reflected by the higher contents of organic carbon, total nitrogen, phosphorus, and ferrum) ( Table 1 ), which might reduce the inter-dependent relationships between different functional groups in acquiring nutrients for their growth [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lough Feeagh (53⁰56'N, 9⁰34'W) is a monomictic, oligotrophic and humic freshwater lake located on the west coast of Ireland with a surface area of 3.95 km 2 , a maximum depth of 46.8 m, an average depth of 14.5 m and an average retention time of 172 days (Hoke et al, 2020).…”
Section: Study Sitementioning
confidence: 99%